Online Course: Application Models in the Educational Process - N. V. Grechushkina (Moscow Polytechnic University, 2021)
Digitalization of education and the development of electronic pedagogy as a branch of pedagogical science are the conditions that actualize the analysis of online courses application mo-dels which is the purpose of this study. Based on the analysis of scientific pedagogical literature, the article addresses the typology of online courses integration models implemented in the traditional (face-to face) educational process. The author has studied and summarized the various approaches to selecting  integration models of online courses  in Russian and  foreign scientific and pedagogical literature and developed a typology of patterns of online courses application based on three criteria: the organization of the educational process (characteristics: the character of the online course incorporating in the educational process, a way of organizing the educational process), the contents of traditional face-to-face and online components in the learning content (characteristics: a change in the structure of educational process, forms and methods of training), and the organization of interaction between the subjects of the educational process (characteristics: organization of pedagogical support, organization of pedagogical interaction between the subjects). This approach made it possible to pinpoint thirty-four models of online courses application and  integration. Each model implemented in practice can be identified unambiguously when typologizing by one characteristic of the corresponding criterion and refer to several types when considering its different characteristics.